2010
DOI: 10.1186/1471-2458-10-510
|View full text |Cite
|
Sign up to set email alerts
|

Women's knowledge and attitudes regarding alcohol consumption in pregnancy: a national survey

Abstract: BackgroundAlcohol exposure in pregnancy is a common and modifiable risk factor for poor pregnancy and child outcomes. Alcohol exposure in pregnancy can cause a range of physical and neurodevelopmental problems in the child including the Fetal Alcohol Spectrum Disorders (FASD). In order to improve prevention strategies, we sought to describe the knowledge and attitudes of women of childbearing age regarding alcohol consumption during pregnancy and its effects on the fetus.MethodsWe conducted a national cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 14 publications
6
58
1
4
Order By: Relevance
“…Women with higher levels of education have higher levels of knowledge [23] but despite this, are more likely to drink alcohol in pregnancy. Education level is an independent predictor of alcohol use in pregnancy but is not explained solely by women's current alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Women with higher levels of education have higher levels of knowledge [23] but despite this, are more likely to drink alcohol in pregnancy. Education level is an independent predictor of alcohol use in pregnancy but is not explained solely by women's current alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with data from countries where FASD public awareness campaigns have been widely conducted, knowledge is higher and attitudes more strongly favour caution about alcohol use during pregnancy (45, 46). In our sample, more educated women demonstrated more accurate knowledge about the specific effects of alcohol consumption in pregnancy (26, 45). However in St. Petersburg, a major city where women were better educated, women’s attitudes were more favourable towards alcohol consumption during pregnancy compared to more rural Nizhny Novgorod Region locations, when we expected to find the opposite.…”
Section: Discussionmentioning
confidence: 91%
“…While the majority of studies found correlations between alcohol beliefs and risky drinking (21, 22), there are mixed data about effects of knowledge. Several studies reported that increased knowledge had limited, if any, effects on attitudes and alcohol consumption (2326). In addition, a study of general health control beliefs in Russian population reported weaker and less consistent associations between beliefs and health behaviors in Russia compared to other countries (27).…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo Kesmodel y Schioler Kesmodel (2002) hallaron que la abstinencia durante la gestación era más Sin embargo, a diferencia de lo reportado en otros estudios (Kesmodel & Schioler Kesmodel, 2002;Peadon et al, 2010), la información respecto a las consecuencias negativas del consumo durante la gestación y las actitudes respecto al consumo durante ese período se encontraron fuertemente Teniendo en cuenta esta perspectiva amplia de información, la misma puede considerarse como uno de los factores constitutivos de las actitudes (Ajzen & Fishbein, 2005), en las que confluyen los aspectos cognitivo-representacionales y experienciales-emotivos ligados a un objeto social, lo cual explicaría la fuerte relación encontrada entre esas variables.…”
Section: Discussionunclassified